2018
DOI: 10.3389/fpsyg.2018.01169
|View full text |Cite
|
Sign up to set email alerts
|

Improved Self-Esteem in Artists After Participating in the “Building Confidence and Self-Esteem Toolbox Workshop”

Abstract: Performing and creative artists have unique occupational and lifestyle stresses and challenges that can negatively affect self-esteem. Low self-esteem not only has serious implications for their psychological and physical health, it can also affect their performance, and creativity. There is a need to establish effective interventions to deal with this issue. To the best of our knowledge, there are no reported studies specific to workshops or interventions on enhancing self-esteem for artists. The Al and Malka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(52 reference statements)
0
1
0
2
Order By: Relevance
“…Finally, we found that furloughed individuals often considered their skills to be inferior to the skills of their non-furloughed colleagues. This may lead to low self-esteem and confidence problems (Shack et al, 2018 ) which, if not addressed, may influence overall organizational climate by diving the workforce and negatively affecting their relationships (Szulc, 2020 ). Consistently, employers may consider implementing return-to-work interviews where employee's value and contribution to the organization is emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that furloughed individuals often considered their skills to be inferior to the skills of their non-furloughed colleagues. This may lead to low self-esteem and confidence problems (Shack et al, 2018 ) which, if not addressed, may influence overall organizational climate by diving the workforce and negatively affecting their relationships (Szulc, 2020 ). Consistently, employers may consider implementing return-to-work interviews where employee's value and contribution to the organization is emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…De este modo, consideramos que la autoestima es un factor influyente en el bienestar psicológico de estudiantes y músicos profesionales que repercute en su satisfacción vital, específicamente entre los más jóvenes. Asimismo, al haber observado que aquellas personas con una autoestima más alta tienen una mejor percepción de su satisfacción con la vida, creemos que serán más eficientes para afrontar las múltiples situaciones estresantes, desafíos y adversidades que en última instancia experimentan los estudiantes de música y músicos profesionales (Ascenso et al, 2018;Berchtold-Neumann, 2018;Cruder et al, 2020;Duy & Yıldız, 2019;Haraldsen, et al, 2020;Matei et al, 2018;Pecen et al, 2018;Shack et al, 2018).…”
Section: Discusión Y Conclusionesunclassified
“…Específicamente, esta tensión y exposición elevada derivada de los retos y desafíos profesionales puede influir negativamente en la autoestima de estudiantes de música y músicos profesionales. Asimismo, una baja autoestima puede repercutir negativamente en el bienestar psicológico y físico, pudiendo afectar a su rendimiento y creatividad (Shack et al, 2018).…”
Section: Introductionunclassified